Explorers of the Black Box : the Search for the Cellular Basis of Memory. - Allport, Susan (Open Road Distribution, 2016)
Explorers of the Black Box is a scientific adventure story. The "Black Box" is the brain. The "Explorers" are neuroscientists in search of how nerve cells record memories, and they are as ruthless and dauntless as any soldiers of fortune. The book centers around the early, often-controversial research Nobel Prize-winner Eric Kandel. It takes readers behind the scenes of laboratories at Woods Hole, Columbia, Yale, and Princeton to create an absorbing account of how the brain works and of how science itself works.